EPILEPSY IN CHILDREN WITH MUCOPOLYSACCHARIDOSIS: EPIDEMIOLOGY, CLINICAL AND ELECTROENCEPHALOGRAPHIC FEATURES - Victoriya A. Aysina; Aleksandr A. Buksh; Ludmila M. Kuzenkova; Olga V. Kozhevnikova; Vladislav V. Lebedev; Andrey A. Gazaryan; Tatyana V. Podkletnova; Sofiya G. Popovich ("Paediatrician" Publishers LLC, 2018)
The current knowledge of the causes and progression of epilepsy in patients with different types of mucopolysaccharidosis are presented. The article discusses the dynamics of electroencephalographic changes with age and in connection with the disease progression.